2002
DOI: 10.1071/ar01106
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of growth and development of diverse legume species in APSIM

Abstract: This paper describes the physiological basis and validation of a generic legume model as it applies to 4 species: chickpea (Cicer arietinum L.), mungbean (Vigna radiata (L.) Wilczek), peanut (Arachis hypogaeaL.), and lucerne (Medicago sativa L.). For each species, the key physiological parameters were derived from the literature and our own experimentation. The model was tested on an independent set of experiments, predominantly from the tropics and subtropics of Australia, varying in cultivar, sowing date, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
163
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(181 citation statements)
references
References 0 publications
7
163
0
1
Order By: Relevance
“…Similarly, Sinclair and Muchow (1999) reported apparently low RUE values in different grain legumes. Higher RUE values have been found for warm-season grain legumes such as mungbean (0.94) and peanut (1.20) (Robertson et al 2002a).…”
Section: Ruementioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, Sinclair and Muchow (1999) reported apparently low RUE values in different grain legumes. Higher RUE values have been found for warm-season grain legumes such as mungbean (0.94) and peanut (1.20) (Robertson et al 2002a).…”
Section: Ruementioning
confidence: 98%
“…The model uses a daily time-step and is driven by daily weather inputs. The physiological basis of the generic APSIM-Legume model and its performance for 5 legume species (chickpea, mungbean, peanut, lucerne, and fababean) has been described in detail by Robertson et al (2002a) and Turpin et al (2003).…”
Section: Model Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Boote et al (1998) reported a few methodologies for simulating LAI in soybean (Glycine max L. Merr) crop. While, Robertson et al (2002) gave ordinary crop models relevant to soybean crop. Teruel et al (1997) reported LAI modelling in sugarcane (Saccharum officinarum L.) to different water stress conditions.…”
Section: Leaf Area Index (Lai)mentioning
confidence: 99%
“…For canola, the optimal temperature for its full development is about 20°C, with extreme limits between 12 and 30°C (Robertson et al, 2002;Thomas, 2003).…”
Section: Introductionmentioning
confidence: 99%